A documentary history 1600-1900. Early american women / Nancy Woloch, Barnard College - Woloch, Nancy [et.al] (1992)
Natives and captives, well-ordered families, the colonial economy, women and the Law, religious experiences, the revolutionary era; the young nation, 1800-1860, domestic lives, the school and the Mill, western and Urban Frontiers, mistress and slave, the rform impulse; the lave 19th century, 1860-1900, the women´s war, the reforman impulse, urban wage earners, college women, clubs, causes and reform, the suffrage movement, new woman/new century.